THE RELATIONSHIP BETWEEN LEARNING READINESS AND ACADEMIC BURNOUT IN FULL-DAY SCHOOL STUDENTS AT MAN 2 MODEL PADANGSIDEMPUAN - Shafira Althasya; Nurhayani Nurhayani (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
The purpose of this study was to determine the relationship between learning readiness and student academic burnout at MAN 2 Padangsidempuan Model. This research uses descriptive correlational quantitative method. The study population was 248 students and the research sample was 151 consisting of 56 male students and 95 female students. The sample was taken using the Simple Random Sampling method and using the Isaac and Michael formula with an error tolerance limit of 5% (0.05). Data collection instruments used observation, learning readiness scale and academic burnout scale. The data in this study were analysed using descriptive analysis techniques with statistical calculations in the form of frequencies and percentages and correlation analysis techniques using Pearson's Product Moment Correlation formula processed with the SPSS (Statistical Product and Service Solution) computer program relase 25.0 for windows. Based on the results of data processing, there is a significant negative relationship between learning readiness and academic burnout in class XI IPA students at MAN 2 Padangsidempuan Model with a correlation coefficient of -0.725 which indicates that there is a relationship between learning readiness and student academic burnout. The negative correlation coefficient number (-) indicates a relationship with a negative direction, namely the higher the readiness to learn, the lower the students' academic burnout, and vice versa, the lower the readiness to learn, the higher the students' academic burnout.